Effects of Higher Percentage of Stone Dust Used as a Fine Aggregate in Concrete and Variation of Strength due to the Variation of Cement Content and W/C Ratio - Paul, Bikram; Ghosh, Kushal; Ghosh, Partha (Asian Journal of Engineering and Applied Technology, 2018)
Sustainability and Unavailability play an important role while we choose material for manufacturing of concrete. Nowadays, both Central and State Govt. have taken legal action on the extraction of sand from the river bed due to the bad impacts on the river like changes the shape, slope of the bed and also in the channel morphology. Due to the implementation of this type of law, legal sand quarries did not able to make balance with the rapid growth of the construction industry. That’s why, to make profit and supply extra needs of sand to the concrete industry “Sand Mafias” involved into the illegal trades of the sand. To counteract these sorts of socio-economic problems, we have to go for an alternative fine aggregate. Though it may not be possible to replace fully, we have to concentrate on the sand being replaced by the high percentage of alternative fine aggregate. Stone dust is a by-product from rock crusher and it can be recycled by using it in the concrete and maintained the sustainability. As stone dust has acceptable properties of fine aggregate sand with regard to shape and texture, it can be thought of as an alternate fine aggregate but research is needed on the extent of sand replacement by stone dust. The present study is done keeping in mind the use of stone dust as high as possible. That’s why two Design Mix have been designed M20 and M25. For M20 grade of concrete sand has been replaced by stone dust 25%, 30% and 35% by volume and the basic strength properties of concrete have been investigated for the above replacements like compressive strength, flexural strength, split tensile strength etc. In case of M25 grade of concrete 30%, 40% and 50% replacement of sand have been done and variation cement content and water-cement ratio has been done by comparing the target mean strength of M25 grade of concrete.